2003
DOI: 10.1203/01.pdr.0000042441.34920.77
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low versus High Intravenous Amino Acid Intake on Very Low Birth Weight Infants in the Early Neonatal Period

Abstract: Greater protein intakes are required than have been commonly used to achieve fetal in utero protein accretion rates in preterm neonates. To study the efficacy and safety of more aggressive amino acid intake, we performed a prospective randomized study in 28 infants [mean wt, 946 Ϯ 40 g (SEM)] of 1 (low amino acid intake, LAA) versus 3 g·kg Ϫ1 ·d Ϫ1 (high amino acid intake, HAA) at 52.0 Ϯ 3.0 h of life. After a minimum of 12 h of parenteral nutrition, efficacy was determined by protein balance and was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 31 publications
3
38
0
2
Order By: Relevance
“…[10][11][12] None of the studies with early AAs administration up to 2.3 g/kg/d reported metabolic acidosis or clinically significant hyperaminoacidemia. 16 Also, the plasma concentrations of all essential AAs and most nonessential AAs increased with early AA administration and were more in concordance with reference ranges from healthy fetuses or breast fed infants. 16 In addition, early parenteral AA intake is associated with a reduction in insulin-treated hyperglycemia 17 and better long-term neurodevelopmental outcomes.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…[10][11][12] None of the studies with early AAs administration up to 2.3 g/kg/d reported metabolic acidosis or clinically significant hyperaminoacidemia. 16 Also, the plasma concentrations of all essential AAs and most nonessential AAs increased with early AA administration and were more in concordance with reference ranges from healthy fetuses or breast fed infants. 16 In addition, early parenteral AA intake is associated with a reduction in insulin-treated hyperglycemia 17 and better long-term neurodevelopmental outcomes.…”
Section: Discussionsupporting
confidence: 68%
“…16 Also, the plasma concentrations of all essential AAs and most nonessential AAs increased with early AA administration and were more in concordance with reference ranges from healthy fetuses or breast fed infants. 16 In addition, early parenteral AA intake is associated with a reduction in insulin-treated hyperglycemia 17 and better long-term neurodevelopmental outcomes. 18 Thus, early PN containing AA supplementation in 24 hours of life has become part of the standard care for VLBW infants.…”
Section: Discussionsupporting
confidence: 68%
“…The preterm infant should have the capacity to metabolize the same amount of amino acids as its postconceptionally age-matched intrauterine counterpart, although the preterm infant misses the maternal metabolic clearance possibility its fetal counterpart has. However, it has been shown that early administration of intravenous amino acids is safe and brings the preterm newborn in an anabolic state [13,14,15]. We have studied immediate and 2-year follow-ups from our own cohort, where we infused 2.4 g of amino acids per kilogram BW per day from birth onwards, compared to a stepwise increment in 2–3 days.…”
Section: Managing Nutrition According To the Latest Guidelines Of Thementioning
confidence: 99%
“…[1][2][3][4][5][6][7][20][21][22]. A recent study reported that early administration of amino-acid improved preterm infant weight with less number of infants below the tenth percentile in the growth curve, but there was a slightly higher incidence of bronchopulmonary dysplasia.…”
Section: Discussionmentioning
confidence: 99%